Perceptions of development - Wallman, Sandra (Cambridge ; New York : Cambridge University Press, 1977)
This book of essays raises a number of important questions concerning development. They all deal with issues that planners and economists have tended to neglect, and examine a range of case-studies where the social and human components of 'development' - and people's own perceptions of it- have clashed with the drive for material improvements with which the term has come to be so widely associate.
Includes index.
Bibliography: p. (197-205)
lje 27/7/18
Loans
Keywords: Economic development; Social history